Associations between seasonal temperature and dementia-associated hospitalizations in New England. (May 2019) - Wei, Yaguang; Wang, Yan; Lin, Cheng-Kuan; Yin, Kanhua; Yang, Jiabei; Shi, Liuhua; Li, Longxiang; Zanobetti, Antonella; Schwartz, Joel D.
Abstract: Human-induced climate change has accelerated in recent decades, causing adverse health effects. However, the impact of the changing climate on neurological disorders in the older population is not well understood. We applied time-varying Cox proportional hazards models to estimate the associations between hospital admissions for dementia and the mean and variability of summer and winter temperatures in New England. We estimated seasonal temperatures for each New England zip code using a satellite-based prediction model. By characterizing spatial differences and temporal fluctuations in seasonal temperatures, we observed a lower risk of dementia-associated hospital admissions in years when local temperatures in either summer (hazard ration [HR] = 0.98; 95% confidence interval [CI]: 0.96, 1.00) or winter (HR = 0.97; 95% CI: 0.94, 0.99) were higher than average, and a greater risk of dementia-associated admissions for older adults living in zip codes with higher temperature variations. Effect modifications by sex, race, age, and dual eligibility were considered to examine vulnerability of population subgroups. Our results suggest that cooler-than-average temperatures and higher temperature variability increase the risk of dementia-associated hospital admissions. Thus, climate change may affect progression of dementia and associated hospitalization costs. Highlights: Lower-than-average temperature and higher temperature fluctuations were associated with an increased risk of dementia hospitalizations. Among the elderly population, low-income and younger aged subgroups were more vulnerable to warmer climate or greater temperature variations. Long-term climate change may affect the progression of dementia and the associated healthcare costs.